Clinical characteristics and outcomes of bullous pemphigoid patients with versus without oral prednisolone treatment. Issue 4 (18th February 2021) - Ujiie, Inkin; Iwata, Hiroaki; Yoshimoto, Norihiro; Izumi, Kentaro; Shimizu, Hiroshi; Ujiie, Hideyuki
Abstract: Bullous pemphigoid (BP) varies in severity and stratified treatments are needed. However, there are no definitive standards for choosing appropriate treatments. To elucidate the factors involved in choosing treatments and the clinical outcomes of BP, we retrospectively reviewed the clinical records of 78 BP patients at a single center. Of the 78 patients, 49 (62.8%) were treated with oral prednisolone (PSL) and 29 (37.2%) were treated without PSL. The patients with older age, lower Bullous Pemphigoid Disease Area Index (BPDAI), and/or lower anti‐BP180NC16a antibody titer at onset tended to be treated without oral PSL. Notably, only 9.1% patients without PSL experienced relapse, whereas 36.7% patients with oral PSL experienced relapse when the PSL was around 0.1 mg/kg. It suggests that the patients with mild disease severity could be well controlled without oral PSL. Receiver–operator curve analysis demonstrated that the cut‐off value for the use of oral PSL was 31 for total BPDAI and was 7 for BPDAI skin urticaria/erythema, with a high (>0.9) area under the curve. Notably, none of the patients who were negative for the anti‐BP180NC16a antibody at onset experienced relapse even though they were treated without PSL. In conclusion, in BP patients who were negative for anti‐BP180NC16a antibody at onset, with a total BPDAI score of less than 31 or with an urticaria/erythema score of less than 7 can be treated without PSL. When the PSL is tapered to around 0.1 mg/kg, we should carefully monitor the patients to detect relapse.